Investigating English First Additional Language educators’ reading comprehension practices in selected schools in Gauteng, South Africa - Tilla Olifant; MP Cekiso; Naomi Boakye (South African Journal of Education, 2022)
Educators’ reading comprehension instructional practices have been identified as 1 of the factors that contribute to learners’ poor reading comprehension performance. To this end, several studies were conducted to identify and analyse educators’ practices while teaching reading comprehension. As a result, the aim of the study reported on here was to investigate educators’ teaching practices when teaching reading comprehension in order to diagnose challenges and then make recommendations. The study was qualitative in nature with a case study design. For the purpose of data collection, 3 Grade 9 English First Additional Language (FAL) educators were purposively chosen. The observation data collection method was followed and content analysis was used to analyse data. With regard to the choice of reading comprehension strategies, the findings reveal that the educators did not appear to have a thorough knowledge of reading comprehension strategies. In the observed lessons, the reading comprehension strategies were neither applied explicitly nor implicitly. Educators tended to change the reading lessons into vocabulary lessons. The findings further reveal that the educators relied on traditional questioning techniques that did not engage learners with the text. Thus, the reading comprehension support, motivation and feedback from educators were limited. The main recommendation is for teacher training institutions and universities to play a more active role in developing both pre-service and in-service educators’ reading comprehension instructional practices.